Preparation method and application of FeCo catalyst

The FeCo catalyst prepared by co-precipitation method and reduction carbonization reaction solves the problem of poor stability of existing catalysts, achieves high catalytic activity and stability, and is suitable for multiple reuses of Fischer Tropsch synthesis.

CN119608197APending Publication Date: 2025-03-14CHINA ENERGY GRP NINGXIA COAL IND CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411685190.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The catalysts used in Fischer-Tropsch synthesis in the prior art have poor stability, resulting in their inactivation during multiple reuses, increasing the cost of use.

Method used

A carrier precursor with double additives was prepared by co-precipitation method, and Fe and Co were supported on the support, and a mixture of ammonia, methanol and hydrogen was subjected to a reduction carbonization reaction to prepare a FeCo catalyst.

Benefits of technology

The prepared FeCo catalyst has high thermal stability, mechanical strength, catalytic activity and selectivity, and can be reused multiple times in Fischer Tropsch synthesis reaction, reducing the cost of use.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119608197A_ABST
    Figure CN119608197A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method and application of a FeCo catalyst. The preparation method of the FeCo catalyst comprises the following steps: mixing a first auxiliary agent, a second auxiliary agent and an aluminum salt, and carrying out a co-precipitation reaction to obtain a carrier precursor; dropwise adding a Fe-containing salt solution and a Co-containing ammonia complex solution into the carrier precursor for the first time in a parallel flow manner, and stirring for the first time to obtain a mixture; performing ammonia distillation, drying and calcining on the mixture to obtain a FeCo catalyst precursor; and carrying out reduction carbonization reaction on the FeCo catalyst precursor by using a mixed gas containing ammonia gas, methanol and hydrogen to obtain the FeCo catalyst. The method for preparing the FeCo catalyst has the advantage of low cost, and the FeCo catalyst prepared by adopting the method disclosed by the invention not only has high thermal stability, but also has relatively high catalytic activity and relatively high hydrocarbon product selectivity, and has a good industrial application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of catalysts, and in particular to a preparation method of a FeCo catalyst and application thereof. Background Art

[0002] The Fischer-Tropsch synthesis reaction is a process in which synthesis gas H2 and CO are converted into hydrocarbons under the action of a catalyst. The reaction equation is as follows:

[0003] nCO+2nH2→C n H 2n +nH2O

[0004] nCO+(2n+1)H2→C n H 2n+2 +nH2O

[0005] Under the appropriate temperature, pressure and catalyst, Fischer-Tropsch synthesis can synthesize hydrocarbon compounds with different carbon numbers. Hydrocarbon compounds can be processed to obtain other chemicals. Therefore, Fischer-Tropsch synthesis can realize the energy conversion of coal, natural gas, biomass, etc. through synthesis gas to oil. Fischer-Tropsch synthesis technology can be divided into high-temperature Fischer-Tropsch and low-temperature Fischer-Tropsch according to the reaction temperature: the reaction temperature of high-temperature Fischer-Tropsch is greater than 300℃; the reaction temperature of low-temperature Fischer-Tropsch is less than 280℃, among which the reaction temperature of Fischer-Tropsch synthesis of iron-based catalyst is 250-280℃, and the reaction temperature of Fischer-Tropsch synthesis of cobalt-based catalyst is 200-230℃. Iron-based catalysts have the advantages of low price, good toxicity resistance and wide reaction conditions; cobalt-based catalysts have unique advantages for the growth of long-chain hydrocarbons and have high catalytic reaction activity.

[0006] CN105478128B discloses a Fischer-Tropsch synthesis iron-based catalyst with high anti-wear performance and high reaction activity and a preparation method thereof, wherein the catalyst is mainly active component of Fe, and structural additives, anti-sintering additives and electronic additives are added to the catalyst, and the catalyst has high mechanical strength and anti-wear performance. However, the overall activity of the catalyst is low, and the methane selectivity is high. The catalyst does not pay attention to the stability of the prepared catalyst.

[0007] CN102441386A discloses a novel Fischer-Tropsch synthesis method. The patent provides a cobalt-based catalyst with porous nano-titanium oxide and silicon oxide composite particles prepared by a sol-gel method as a carrier. The catalyst can achieve low selectivity for carbon dioxide and methane, and can also produce C with high selectivity. 20 ~C 36 However, the catalyst stability and strength were not further explored.

[0008] Therefore, it is crucial to develop a FeCo catalyst with high catalytic activity and strong stability. Summary of the invention

[0009] The main purpose of the present invention is to provide a preparation method of a FeCo catalyst and application thereof, so as to solve the problem of poor stability of catalysts used for Fischer-Tropsch synthesis in the prior art.

[0010] In order to achieve the above-mentioned object, according to the first aspect of the present invention, a method for preparing a FeCo catalyst is provided, the preparation method comprising: mixing a first auxiliary agent, a second auxiliary agent and an aluminum salt for a coprecipitation reaction to obtain a carrier precursor; dripping a Fe-containing salt solution and a Co-containing ammonia complex solution into the carrier precursor in parallel for the first time and stirring for the first time to obtain a mixture; distilling ammonia, drying and calcining the mixture to obtain a FeCo catalyst precursor; and performing a reduction carbonization reaction on the FeCo catalyst precursor using a mixed gas containing ammonia, methanol and hydrogen to obtain the FeCo catalyst.

[0011] Furthermore, the preparation method of the carrier precursor comprises the following steps:

[0012] The first auxiliary agent, the second auxiliary agent, the aluminum salt and deionized water are mixed to obtain a solution A;

[0013] The solution A is added dropwise to the sodium carbonate solution for a second time and stirred for a second time to obtain a suspension B, and the addition is stopped when the pH of the suspension B is 3.5 to 5;

[0014] The sodium carbonate solution is added dropwise to the suspension B for the third time and stirred for the third time to obtain a suspension C, and the addition is stopped when the pH of the suspension C is 8.5 to 10;

[0015] The suspension C is stirred, filtered and washed for the fourth time to obtain a filter cake;

[0016] Adding the deionized water to the filter cake to evenly disperse the filter cake to obtain the carrier precursor;

[0017] Preferably, the concentration of the sodium carbonate is 0.5 to 3 mol / L;

[0018] More preferably, the concentration of the sodium carbonate is 1 to 2 mol / L;

[0019] Preferably, the second dripping speed is 20-40 mL / min;

[0020] More preferably, the speed of the second addition is 25 to 35 mL / min;

[0021] Preferably, the rate of the third addition is 30 to 60 mL / min;

[0022] Preferably, the speed of the second stirring is 150-400 r / min;

[0023] Preferably, the speed of the third stirring is 150-400 r / min.

[0024] Furthermore, the method for preparing the solution of the Co-containing ammonia complex comprises: mixing a Co-containing salt solution and ammonium carbonate-ammonia water to obtain the solution of the Co-containing ammonia complex;

[0025] Preferably, the Co-containing salt solution is selected from any one of the following: cobalt carbonate, cobalt sulfate or basic cobalt carbonate;

[0026] Preferably, the molar ratio of Co ions in the Co-containing salt solution to the ammonia water in the ammonium carbonate-ammonia water is: (0.5-1):30.

[0027] Furthermore, the Fe-containing salt solution is selected from any one of the following: ferric nitrate, ferric sulfate, ferric chloride or ferric acetate;

[0028] Preferably, the aluminum salt is selected from any one of the following: aluminum nitrate nonahydrate, aluminum sulfate 18hydrate or anhydrous aluminum chloride;

[0029] Preferably, the molar ratio of the iron ions in the Fe-containing salt solution, the Co ammonia complex in the Co ammonia complex solution, and the aluminum ions in the aluminum salt is (0.25-0.75):(0.1-0.5):1;

[0030] More preferably, the molar ratio of the iron ions in the Fe-containing salt solution, the Co ammonia complex in the Co ammonia complex solution, and the aluminum ions in the aluminum salt is (0.4-0.6):(0.15-0.3):1;

[0031] Preferably, the speed of the first dropping is 5 to 20 mL / min.

[0032] Furthermore, the above drying includes air drying and vacuum drying;

[0033] Preferably, the temperature of the above-mentioned blast drying is 100-140°C and the time is 8-12h;

[0034] More preferably, the temperature of the above-mentioned blast drying is 110-120°C and the time is 10-12h;

[0035] Preferably, the vacuum drying is carried out at a temperature of 50 to 80° C. and for a time of 12 to 24 hours.

[0036] More preferably, the vacuum drying is carried out at a temperature of 60 to 70° C. and for a time of 15 to 20 hours.

[0037] Furthermore, the calcination temperature is 400-650° C. and the calcination time is 4-8 hours.

[0038] Furthermore, the ammonia evaporation temperature is 50-80°C;

[0039] Preferably, when the pH value of the mixture is 5 to 6.5, the ammonia evaporation is stopped.

[0040] Furthermore, the first auxiliary agent is selected from any one of the following: metal salts of Cu, Zn, Ti, Mo, Ce or Mn;

[0041] Preferably, the second auxiliary agent is selected from any one of the following: magnesium nitrate, barium nitrate, calcium nitrate or strontium nitrate;

[0042] Preferably, the molar ratio of the metal ion in the first auxiliary agent, the metal ion in the second auxiliary agent and the aluminum ion in the aluminum salt is (0.005-0.05):(0.01-0.1):1;

[0043] More preferably, the molar ratio of the metal ion in the first auxiliary agent, the metal ion in the second auxiliary agent and the aluminum ion in the aluminum salt is (0.02-0.03):(0.05-0.08):1.

[0044] Furthermore, the volume ratio of the ammonia, the methanol and the hydrogen is (1-3):(1-4):15;

[0045] Preferably, the reaction conditions of the reduction carbonization are as follows: the mixed gas space velocity is 4000-8000 mL / (g-cat.·h), the temperature is 250-350° C., the pressure is 1.5-3 MPa, and the time is 12-48 h.

[0046] In order to achieve the above object, according to a second aspect of the present invention, the FeCo catalyst prepared by the above preparation method is used in Fischer-Tropsch synthesis.

[0047] By applying the technical solution of the present invention, a carrier precursor with dual additives is prepared by a co-precipitation method, Fe and Co are further loaded on the carrier precursor, and a mixed gas containing ammonia, methanol and hydrogen is used to carry out a reduction carbonization reaction to prepare a catalyst with strong thermal stability, and the catalyst can be repeatedly used in the Fischer-Tropsch synthesis reaction.

[0048] Among them, the metal salt of the dual auxiliary agent and the metal salt that forms the carrier are prepared by co-precipitation method to prepare the carrier precursor, which strengthens the interaction between the auxiliary agent and the carrier, and loads the active substance before the two form a strong bonding relationship. After the prepared catalyst is post-treated, the active center, auxiliary agent and the metal of the carrier are grafted through oxygen bridges, which makes the catalyst have higher catalytic stability.

[0049] The dual active centers are loaded on the carrier in a competitive manner, which effectively reduces the possibility of metal agglomeration in the active centers and improves the activity and stability of the catalyst. The catalyst has high reaction activity and catalytic stability under a wide range of reaction conditions.

[0050] A mixture of ammonia, methanol and hydrogen is used for reduction carbonization. Ammonia can react with Fe2O3 to generate FexN intermediate, and FexN is further reduced and carbonized to FexC. The presence of FexN makes it easier for iron species to be reduced and carbonized to FexC active phase. Methanol is cheap and readily available. Using methanol instead of CO for carbonization reduces the cost of reducing gas. The prepared catalyst has excellent catalytic activity and stability in Fischer-Tropsch synthesis.

[0051] The method for preparing the FeCo catalyst of the present invention has the advantage of low cost, and the FeCo catalyst prepared by the method of the present invention not only has strong thermal stability, but also has high catalytic activity and high hydrocarbon product selectivity, and has good industrial application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0052] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:

[0053] Figure 1 The SEM image of the catalyst prepared according to Example 4 of the present invention is shown. DETAILED DESCRIPTION

[0054] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.

[0055] As mentioned in the background art, the FeCo catalyst prepared by the prior art has poor stability and cannot be reused many times, which increases the use cost of the catalyst. In the present invention, the inventors try to use a coprecipitation method to prepare a carrier precursor with double additives, continue to load Fe and Co on the carrier precursor, and use a mixed gas containing ammonia, methanol and hydrogen to perform a reduction carbonization reaction to prepare a FeCo catalyst. The FeCo catalyst has strong stability and high catalytic activity and C 5+ Selectivity. Therefore, the protection scheme of the present invention is proposed.

[0056] In a first typical embodiment of the present invention, a method for preparing a FeCo catalyst is provided, the preparation method comprising: mixing a first auxiliary agent, a second auxiliary agent and an aluminum salt for a coprecipitation reaction to obtain a carrier precursor; dripping a Fe-containing salt solution and a Co-containing ammonia complex solution into the carrier precursor in parallel for a first time and stirring for a first time to obtain a mixture; distilling ammonia, drying and calcining the mixture to obtain a FeCo catalyst precursor; and performing a reduction carbonization reaction on the FeCo catalyst precursor using a mixed gas containing ammonia, methanol and hydrogen to obtain the FeCo catalyst.

[0057] In a preferred embodiment of the present invention, the preparation method of the above-mentioned carrier precursor comprises the following steps: mixing the above-mentioned first auxiliary agent, the above-mentioned second auxiliary agent, the above-mentioned aluminum salt and deionized water to obtain solution A; adding the above-mentioned solution A to the sodium carbonate solution for a second time and stirring it for a second time to obtain suspension B; and when the pH of the above-mentioned suspension B is 3.5-5, stopping the dropping; adding the above-mentioned sodium carbonate solution to the above-mentioned suspension B for a third time and stirring it for a third time to obtain suspension C; when the pH of the above-mentioned suspension C is 8.5-10, stopping the dropping; stirring, filtering and washing the above-mentioned suspension C for a fourth time to obtain a filter cake; adding the above-mentioned deionized water to the above-mentioned filter cake to make the above-mentioned filter cake evenly dispersed to obtain the above-mentioned carrier precursor.

[0058] Aluminum salt is used as the main component of the carrier precursor to prepare the carrier of the catalyst. In a preferred embodiment of the present invention, the aluminum salt is selected from any one of the following: aluminum nitrate nonahydrate, aluminum sulfate 18hydrate or anhydrous aluminum chloride. The carrier plays a key role in the catalyst. It not only provides a huge surface area, so that the active metal (such as Fe and Co) can be evenly dispersed on the surface of the carrier, increasing the contact opportunity between the metal and the reactant, thereby improving the catalytic activity, but also provides a certain thermal stability, mechanical strength and anti-sintering performance, so that the catalyst maintains its structural and functional stability during the reaction. Aluminum salt will be converted into aluminum oxide (Al2O3) after calcination. Aluminum oxide is a commonly used catalyst carrier with good thermal stability and mechanical strength. It can withstand the high temperature and high pressure conditions in the Fischer-Tropsch synthesis process, while avoiding the aggregation of active metals due to sintering, and maintaining the activity and selectivity of the catalyst.

[0059] Among them, the addition of the first auxiliary agent and the second auxiliary agent can further optimize the structure of the catalyst and improve its selectivity and stability in Fischer-Tropsch synthesis. In a preferred embodiment of the present invention, the first auxiliary agent is selected from any one of the following: metal salts of Cu, Zn, Ti, Mo, Ce or Mn; the second auxiliary agent is selected from any one of the following: magnesium nitrate, barium nitrate, calcium nitrate or strontium nitrate; the use of the first auxiliary agent can promote its interaction with the carrier alumina (prepared by aluminum salt), thereby enhancing the stability of the carrier and improving the dispersibility and stability of the active metal.

[0060] The use of the above-mentioned second additive can enhance the mechanical strength of the carrier alumina (prepared by aluminum salt), improve the overall structural stability of the catalyst by forming a complex of alkaline earth metal oxide and alumina, and prevent sintering under reaction conditions. At the same time, these additives may also affect the distribution and selectivity of the product by providing additional acidic or basic sites.

[0061] The ratio of the above-mentioned auxiliary agent and the aluminum salt plays an important role in preparing a catalyst with high stability. In a preferred embodiment of the present invention, the molar ratio of the metal ions in the above-mentioned first auxiliary agent, the metal ions in the above-mentioned second auxiliary agent and the aluminum ions in the above-mentioned aluminum salt is (0.005-0.05): (0.01-0.1): 1. In a more preferred embodiment of the present invention, the molar ratio of the metal ions in the above-mentioned first auxiliary agent, the metal ions in the above-mentioned second auxiliary agent and the aluminum ions in the above-mentioned aluminum salt is (0.02-0.03): (0.05-0.08): 1. The use of this ratio to prepare the FeCo catalyst enables the auxiliary agents (the first auxiliary agent and the second auxiliary agent) to be evenly distributed on the carrier (alumina), avoiding the inconsistent catalyst properties caused by local excess, and increasing the specific surface area and the number of active sites of the catalyst. At the same time, an appropriate amount of auxiliary agent can adjust the electronic structure of the carrier and the active metal, optimize the reduction state and surface state of the active metal, thereby improving the catalytic activity and product selectivity.

[0062] By controlling the ratio of the additive to the aluminum salt, the thermal stability and mechanical strength of the catalyst can be enhanced, the integrity of the carrier structure can be ensured, and the strong bond between the additive and the carrier can be ensured, which is not easy to fall off, thereby improving the durability of the catalyst under reaction conditions.

[0063] The above sodium carbonate is used as a coprecipitant in the process of preparing the catalyst. When the carrier precursor is prepared by the coprecipitation method, sodium carbonate reacts with aluminum salt to generate a precipitate. When solution A (containing aluminum salt and auxiliary agent) is slowly added dropwise to the sodium carbonate solution, sodium carbonate reacts with aluminum ions to form aluminum carbonate precipitation. This coprecipitation reaction helps to form a carrier precursor with a specific structure and performance, providing a good basis for the subsequent loading of active metals (Fe and Co).

[0064] The amount of sodium carbonate added and the conditions of use (such as pH control) have an important influence on the pore structure of the carrier. By adjusting the concentration of sodium carbonate and the conditions of addition, a carrier with a suitable pore size and pore volume can be prepared, which is crucial for increasing the surface area of ​​the catalyst, increasing the dispersion of active metals, and improving the mechanical strength and thermal stability of the catalyst. In the Fischer-Tropsch synthesis reaction, a high specific surface area and a good pore structure can provide more active sites, which is conducive to the adsorption of reactants and the desorption of products, thereby improving catalytic activity and stability.

[0065] In a preferred embodiment of the present invention, the concentration of the sodium carbonate is 0.5-3 mol / L; in a more preferred embodiment of the present invention, the concentration of the sodium carbonate is 1-2 mol / L. The addition of sodium carbonate can control the pH value of the solution. Accurate control of the pH value can enhance the interaction between the additive and the carrier, form a stronger bond, and help form uniformly dispersed metal oxides, avoid excessive agglomeration of active metals, and improve the activity and stability of the catalyst.

[0066] The present invention adopts a reverse dripping method to prepare a carrier precursor, that is, solution A is first dripped (second dripping) into a sodium carbonate solution to obtain a suspension B, and then the sodium carbonate solution is reversely dripped (third dripping) into the suspension B. This method can control the pH value and metal ion concentration in the solution, so that the precipitation process is carried out in a wider pH range, thereby avoiding uneven properties of the precipitate caused by excessively high or low local pH values, and ensuring that the active metal is evenly distributed on the carrier surface.

[0067] Controlling the speed of the second and third dripping in the present invention can optimize the precipitation process (too fast a dripping speed may cause the precipitation to quickly form a large number of small particles, while too slow a speed may generate larger particles.), promote the formation of a carrier precursor with a suitable particle size, uniform metal ion distribution and a stable structure, and then prepare a Fischer-Tropsch synthesis FeCo catalyst with high thermal stability, mechanical strength, catalytic activity and selectivity. Therefore, in a preferred embodiment of the present invention, the speed of the second dripping is 20 to 40 mL / min. In a more preferred embodiment of the present invention, the speed of the second dripping is 25 to 35 mL / min; in a preferred embodiment of the present invention, the speed of the third dripping is 30 to 60 mL / min.

[0068] The first stirring in the above-mentioned co-current dripping process can promote uniform mixing of active metals (Fe and Co), prevent agglomeration, and can also control the reaction rate and improve the preparation efficiency and the activity and stability of the catalyst. The above-mentioned second stirring and third stirring can promote uniform mixing, control the morphology of the precipitate and prevent agglomeration, and finally achieve uniform loading of active metals on the carrier, forming a Fischer-Tropsch synthesis FeCo catalyst with high thermal stability, mechanical strength, catalytic activity and product selectivity. The purpose of the fourth stirring is to make the above-mentioned filter cake dispersed evenly to obtain the above-mentioned carrier precursor.

[0069] In a preferred embodiment of the present invention, the speed of the second stirring is 150-400 r / min. The speed of the third stirring is 150-400 r / min. The stirring speed affects the morphology and particle size of the precipitate formed in the solution. The use of the above stirring speed helps to form smaller and more uniform particles. Too fast stirring will affect the loading effect of ions, while slow stirring may result in larger, uneven precipitated particles, which will ultimately affect the catalytic efficiency. In catalyst preparation, the ideal particle size and morphology are crucial for the uniform distribution of active metals, the formation of pore structure and the performance of the final catalyst.

[0070] In a preferred embodiment of the present invention, the method for preparing the solution of the above-mentioned Co-containing ammonia complex comprises: mixing a Co-containing salt solution and ammonium carbonate-ammonia water to obtain the above-mentioned Co-containing ammonia complex solution; using the Co-containing ammonia complex to prepare the FeCo catalyst not only helps to improve the dispersibility and load control of cobalt, but also improves the stability and activity of the catalyst, while simplifying the preparation process, making it easier to implement in industrial production.

[0071] In a preferred embodiment of the present invention, the above-mentioned Co-containing salt solution is selected from any one of the following: cobalt carbonate, cobalt sulfate or basic cobalt carbonate; in a preferred embodiment of the present invention, the molar ratio of Co ions in the above-mentioned Co-containing salt solution to the above-mentioned ammonium carbonate-ammonia water is (0.5-1): 30. The use of this ratio to prepare the Co-ammonia complex is crucial for forming a stable and uniform cobalt-ammonia complex, and ultimately preparing a FeCo catalyst with excellent performance.

[0072] The first dripping in the present invention is parallel dripping, and the use of parallel dripping is conducive to the uniform competitive loading of Fe and Co on the carrier, and avoids excessive occupation of one of the metals on the carrier surface, resulting in uneven distribution. Controlling the speed of the first dripping (parallel dripping) plays an important role in achieving uniform distribution of active metals on the carrier, regulating chemical reaction conditions, improving the efficiency and quality of catalyst preparation, and ultimately improving the stability and activity of the catalyst. In a preferred embodiment of the present invention, the speed of the above-mentioned first dripping (parallel dripping) is 5 to 20 mL / min. It should be noted that the parallel dripping in the present invention refers to the simultaneous dripping of the above-mentioned Fe-containing salt solution and the above-mentioned Co-containing ammonia complex solution to the above-mentioned carrier precursor at the same speed.

[0073] In the first (cocurrent dripping) process, the Fe ions react with the aluminum oxide in the carrier precursor and are anchored on the carrier by the formation of iron hydroxide. In a preferred embodiment of the present invention, the above-mentioned Fe-containing salt solution is selected from any one of the following: iron nitrate, iron sulfate, iron chloride or iron acetate. In a preferred embodiment of the present invention, the molar ratio of the Co ammonia complex in the above-mentioned Fe-containing salt solution and the above-mentioned Co-containing ammonia complex solution to the aluminum ions in the above-mentioned aluminum salt is (0.25-0.75): (0.1-0.5): 1; in a more preferred embodiment of the present invention, the molar ratio of the Co ammonia complex in the above-mentioned Fe-containing salt solution and the above-mentioned Co-containing ammonia complex solution to the aluminum ions in the above-mentioned aluminum salt is (0.4-0.6): (0.15-0.3): 1. The use of this ratio to prepare the FeCo catalyst has the beneficial effects of high catalytic activity and strong stability.

[0074] The above-mentioned drying includes forced air drying and vacuum drying; wherein the role of forced air drying is to quickly dehydrate the surface of the catalyst with a high water content, so as to reduce the time and energy consumption of subsequent drying. The role of vacuum drying is to remove the moisture inside the catalyst while maintaining the microstructure and stability of the catalyst. In a preferred embodiment of the present invention, the temperature of the forced air drying is 100-140°C, and the time is 8-12h; in a more preferred embodiment of the present invention, the temperature of the forced air drying is 110-120°C, and the time is 10-12h; in a preferred embodiment of the present invention, the temperature of the vacuum drying is 50-80°C, and the time is 12-24h. In a more preferred embodiment of the present invention, the temperature of the vacuum drying is 60-70°C, and the time is 15-20h. Blast drying and vacuum drying under the above conditions can ensure that the moisture in the catalyst precursor is effectively removed, while protecting the structure and performance of the catalyst.

[0075] The role of calcination is to convert the catalyst into a stable metal oxide, remove organic residues, enhance the stability and mechanical strength of the catalyst structure, and provide a suitable precursor for the subsequent reduction carbonization process. In a preferred embodiment of the present invention, the calcination temperature is 400-650°C and the time is 4-8 hours. Calcination under these conditions can make the prepared FeCo catalyst show higher activity, stability and product selectivity in the Fischer-Tropsch synthesis reaction, and has good industrial application prospects.

[0076] The purpose of distilling ammonia on the above mixture is to make the Co loaded on the carrier have better dispersibility, and the particle size of the Co active center is smaller, so that the catalyst has a higher specific surface area, which can avoid the active center of the catalyst from being deactivated due to agglomeration during use, thereby further improving the stability of the FeCo catalyst. In a preferred embodiment of the present invention, the temperature of the distillation of ammonia is 50-80°C; under this condition, the distillation of ammonia has the effect of controlling the load of Co, promoting the uniform dispersion of metal ions (especially Co) and stabilizing the structure of the complex. In a preferred embodiment of the present invention, when the pH value of the above mixture is 5-6.5, the distillation of ammonia is stopped. The purpose of controlling the pH of the mixture is to ensure the load of Co and avoid premature reduction of Fe.

[0077] During the reduction and carbonization process: methanol is cheap and readily available, and methanol is used to replace CO for carbonization, which reduces the cost of reducing gas. Ammonia can react with Fe2O3 to form FexN intermediates, and FexN continues to be reduced and carbonized to FexC. The presence of FexN makes it easier for iron species to be reduced and carbonized to FexC active phase. Hydrogen helps to form a catalyst with high catalytic activity, high thermal stability, high mechanical strength and good selectivity for hydrocarbon products. The volume ratio of ammonia, the above-mentioned methanol and the above-mentioned hydrogen is (1-3):(1-4):15; the catalyst prepared using this ratio of mixed gas has excellent catalytic activity and stability.

[0078] The conditions for controlling the reduction carbonization (such as the composition, temperature, pressure and air velocity of the mixed gas) are carefully controlled to ensure the complete reduction of Fe and Co and the formation of carbides, while avoiding structural damage of the catalyst under high temperature and high pressure. In a preferred embodiment of the present invention, the reaction conditions for the reduction carbonization are: the mixed gas air velocity is 4000-8000mL / (g-cat.·h), the temperature is 250-350°C, the pressure is 1.5-3MPa, and the time is 12-48h.

[0079] In a second typical embodiment of the present invention, there is provided an application of the FeCo catalyst prepared by the above preparation method in Fischer-Tropsch synthesis.

[0080] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.

[0081] Example 1

[0082] The preparation steps of FeCo catalyst for Fischer-Tropsch synthesis are as follows:

[0083] (1) Weigh 12.1 g of copper nitrate trihydrate, 33.3 g of magnesium nitrate hexahydrate, and 750.3 g of aluminum nitrate nonahydrate and dissolve them in 3 L of deionized water. Stir until all the solids are dissolved. This is referred to as solution A.

[0084] (2) Prepare a 1.3 mol / L sodium carbonate solution, referred to as solution B.

[0085] (3) Weigh 404 g of ferric nitrate nonahydrate and dissolve it in 1350 mL of deionized water. Stir until all the solids are dissolved. This is referred to as solution C.

[0086] (4) 1350 mL of 25 wt% ammonia water was measured, 14.3 g of sodium carbonate was added to the ammonia water, and 47.6 g of cobalt carbonate was added to the solution, and stirred until all the solids were dissolved. This was recorded as solution D.

[0087] (5) Add 3 L of solution B to a 10 L flask, add solution A dropwise at a rate of 30 mL / min until the solution pH = 4.5, continue to add solution B dropwise at a rate of 50 mL / min until the solution pH = 9, continue stirring for 2 h, filter to obtain a filter cake, wash the filter cake with deionized water 9 times, put the washed filter cake into a 10 L beaker, add 6 L of deionized water, and stir to evenly disperse the solids. This is recorded as mixture E.

[0088] (6) Solution C and solution D were added dropwise to mixture E at a rate of 10 mL / min in parallel, and stirring was continued for 30 min after the addition was completed.

[0089] (7) Place the flask in step (6) in a water bath, evaporate the ammonia in the solution at 80°C until the pH value of the solution is 6, filter to obtain a filter cake, and wash the filter cake with deionized water until the pH value of the washing solution is 7.

[0090] (8) The washed filter cake was placed in a forced air drying oven at 120°C for 12 hours, and then placed in a vacuum drying oven at 60°C for 15 hours. The dried solid was ground and sieved to make the solid particles ≤ 200 mesh, to obtain solid F.

[0091] (9) The solid F was placed in a tubular furnace and calcined at 500 °C for 5 h in an air atmosphere to obtain a solid catalyst precursor.

[0092] (10) The solid catalyst precursor calcined in step (9) is carbonized in a mixed gas of ammonia, methanol and hydrogen in a volume ratio of 5:20:75. The carbonization conditions are: temperature 280° C., pressure 2.6 MPa, mixed gas space velocity 6000 mL / (g-cat.·h), and constant temperature for 36 hours to obtain the desired catalyst.

[0093] Example 2

[0094] The preparation steps of FeCo catalyst for Fischer-Tropsch synthesis are as follows:

[0095] (1) Weigh 9.7 g of copper nitrate trihydrate, 25.6 g of magnesium nitrate hexahydrate, and 750.3 g of aluminum nitrate nonahydrate and dissolve them in 3 L of deionized water. Stir until all the solids are dissolved. This is referred to as solution A.

[0096] (3) Weigh 323.2 g of ferric nitrate nonahydrate and dissolve it in 1350 mL of deionized water. Stir until all the solid is dissolved. This is referred to as solution C.

[0097] (4) 1350 mL of 25 wt% ammonia water was measured, 13 g of sodium carbonate was added to the ammonia water, and 35.7 g of cobalt carbonate was added to the solution, and stirred until all the solids were dissolved. This was recorded as solution D.

[0098] Other conditions are the same as in Example 1.

[0099] Example 3

[0100] The preparation steps of FeCo catalyst for Fischer-Tropsch synthesis are as follows:

[0101] (1) Weigh 26.1 g of cerium nitrate hexahydrate, 37.8 g of calcium nitrate tetrahydrate, and 750.3 g of aluminum nitrate nonahydrate and dissolve them in 3 L of deionized water. Stir until all the solids are dissolved. This is referred to as solution A.

[0102] (3) Weigh 484.8 g of ferric nitrate nonahydrate and dissolve it in 1350 mL of deionized water. Stir until all the solid is dissolved. This is referred to as solution C.

[0103] (4) 1350 mL of 25 wt% ammonia water was measured, 13 g of sodium carbonate was added to the ammonia water, and 71.4 g of cobalt carbonate was added to the solution, and stirred until all the solids were dissolved. This was recorded as solution D.

[0104] Other conditions are the same as in Example 1.

[0105] Example 4

[0106] The preparation steps of FeCo catalyst for Fischer-Tropsch synthesis are as follows:

[0107] (1) Weigh 21.7 g of cerium nitrate hexahydrate, 30.7 g of calcium nitrate tetrahydrate, and 750.3 g of aluminum nitrate nonahydrate and dissolve them in 3 L of deionized water. Stir until all the solids are dissolved. This is referred to as solution A.

[0108] (3) Weigh 404.0 g of ferric nitrate nonahydrate and dissolve it in 1520 mL of deionized water. Stir until all the solid is dissolved. This is referred to as solution C.

[0109] (4) 1520 mL of 25 wt% ammonia water was measured, 14.6 g of sodium carbonate was added to the ammonia water, and 53.5 g of cobalt carbonate was added to the solution, and stirred until all the solids were dissolved. This was recorded as solution D.

[0110] Other conditions are the same as in Example 1.

[0111] The SEM image of the catalyst is shown in Figure 1 As shown, the base material is spherical, and the FeCo material is loaded on the surface of the carrier, so that the active center is more exposed to the catalytic environment, thereby effectively catalyzing the reaction and making the catalyst have higher activity.

[0112] Example 5

[0113] The preparation steps of FeCo catalyst for Fischer-Tropsch synthesis are as follows:

[0114] (2) Prepare a 1 mol / L sodium carbonate solution, referred to as solution B.

[0115] (5) Add 3 L of solution B to a 10 L flask and add solution A dropwise at a rate of 25 mL / min until the solution pH = 3.5.

[0116] (8) The washed filter cake was placed in a forced air drying oven at 110°C for 12 hours and then placed in a vacuum drying oven at 70°C for 15 hours. The dried solid was ground and sieved to obtain a solid particle size of ≤200 mesh, thereby obtaining solid F.

[0117] Other conditions are the same as in Example 1.

[0118] Example 6

[0119] The preparation steps of FeCo catalyst for Fischer-Tropsch synthesis are as follows:

[0120] (2) Prepare a 1.5 mol / L sodium carbonate solution, referred to as solution B.

[0121] (5) Add 3 L of solution B to a 10 L flask and add solution A dropwise at a rate of 30 mL / min until the solution pH = 5.

[0122] (8) The washed filter cake was placed in a forced air drying oven at 112°C for 10 h, and then placed in a vacuum drying oven at 70°C for 20 h. The dried solid was ground and sieved to make the solid particles ≤ 200 mesh, to obtain solid F.

[0123] Other conditions are the same as in Example 1.

[0124] Example 7

[0125] The preparation steps of FeCo catalyst for Fischer-Tropsch synthesis are as follows:

[0126] (2) Prepare a 2 mol / L sodium carbonate solution, referred to as solution B.

[0127] (5) Add 3 L of solution B to a 10 L flask and add solution A dropwise at a rate of 35 mL / min until the solution pH = 4.5.

[0128] (8) The washed filter cake was placed in a forced air drying oven at 115°C for 11 hours, and then placed in a vacuum drying oven at 65°C for 16 hours. The dried solid was ground and sieved to make the solid particles ≤200 mesh, to obtain solid F.

[0129] Other conditions are the same as in Example 1.

[0130] Example 8

[0131] The preparation steps of FeCo catalyst for Fischer-Tropsch synthesis are as follows:

[0132] (2) Prepare a 2 mol / L sodium carbonate solution, referred to as solution B.

[0133] (5) Add 3 L of solution B to a 10 L flask and add solution A dropwise at a rate of 32 mL / min until the solution pH = 3.5.

[0134] (8) The washed filter cake was placed in a forced air drying oven at 120°C for 11 hours and then placed in a vacuum drying oven at 60°C for 18 hours. The dried solid was ground and sieved to obtain a solid particle size of ≤200 mesh, thereby obtaining solid F.

[0135] Other conditions are the same as in Example 1.

[0136] Example 9

[0137] The preparation steps of FeCo catalyst for Fischer-Tropsch synthesis are as follows:

[0138] (1) Weigh 4.3 g of cerium nitrate hexahydrate, 4.7 g of calcium nitrate tetrahydrate, and 750.3 g of aluminum nitrate nonahydrate and dissolve them in 3 L of deionized water. Stir until all the solids are dissolved. This is referred to as solution A.

[0139] (2) Prepare a 0.5 mol / L sodium carbonate solution, referred to as solution B.

[0140] (3) Weigh 202.0 g of ferric nitrate nonahydrate and dissolve it in 900 mL of deionized water. Stir until all the solid is dissolved. This is referred to as solution C.

[0141] (4) 900 mL of 25 wt% ammonia water was measured, 9.5 g of sodium carbonate was added to the ammonia water, and 23.8 g of cobalt carbonate was added to the solution, and stirred until all the solids were dissolved. This was recorded as solution D.

[0142] (5) Add 3 L of solution B to a 10 L flask, and add solution A at a rate of 20 mL / min until the solution pH is 3.5. Continue to add solution B at a rate of 60 mL / min until the solution pH is 10, continue stirring for 2 h, and filter to obtain a filter cake.

[0143] (8) The washed filter cake was placed in a forced air drying oven at 100°C for 12 hours, and then placed in a vacuum drying oven at 50°C for 24 hours. The dried solid was ground and sieved to make the solid particles ≤ 200 mesh, to obtain solid F.

[0144] Other conditions are the same as in Example 1.

[0145] Example 10

[0146] The preparation steps of FeCo catalyst for Fischer-Tropsch synthesis are as follows:

[0147] (1) Weigh 43.4 g of cerium nitrate hexahydrate, 47.2 g of calcium nitrate tetrahydrate, and 750.3 g of aluminum nitrate nonahydrate and dissolve them in 3 L of deionized water. Stir until all the solids are dissolved. This is referred to as solution A.

[0148] (2) Prepare a 3 mol / L sodium carbonate solution, referred to as solution B.

[0149] (3) Weigh 606.0 g of ferric nitrate nonahydrate and dissolve it in 900 mL of deionized water. Stir until all the solid is dissolved. This is referred to as solution C.

[0150] (4) Measure 2250 mL of 25 wt% ammonia water, add 23.8 g of sodium carbonate to the ammonia water, and add 118.9 g of cobalt carbonate to the solution, and stir until all the solids are dissolved. This is recorded as solution D.

[0151] (5) Add 3 L of solution B to a 10 L flask, and add solution A at a rate of 40 mL / min until the solution pH is 3.5. Continue to add solution B at a rate of 30 mL / min until the solution pH is 8.5, continue stirring for 2 h, and filter to obtain a filter cake.

[0152] (8) The washed filter cake was placed in a forced air drying oven at 140°C for 8 hours and then placed in a vacuum drying oven at 80°C for 12 hours. The dried solid was ground and sieved to obtain solid particles ≤ 200 mesh, thereby obtaining solid F.

[0153] Other conditions are the same as in Example 1.

[0154] Embodiment 11

[0155] The preparation steps of FeCo catalyst for Fischer-Tropsch synthesis are as follows:

[0156] (5) Solution B was added dropwise at a rate of 45 mL / min until the pH of the solution reached 9, and stirring was continued for 2 h. The filter cake was obtained by suction filtration.

[0157] (6) Solution C and solution D were added dropwise to mixture E at a rate of 5 mL / min in parallel, and stirring was continued for 30 min after the addition was completed.

[0158] (7) Place the flask in step (6) in a water bath, evaporate the ammonia in the solution at 70°C until the pH value of the solution is 6, filter to obtain a filter cake, and wash the filter cake with deionized water until the pH value of the washing solution is 7 (the pH value of the washing solution is detected to determine the residual ion content in the washing solution, thereby determining whether the filter cake is cleaned and whether there are no residual ions).

[0159] Other conditions are the same as in Example 1.

[0160] Example 12

[0161] The preparation steps of FeCo catalyst for Fischer-Tropsch synthesis are as follows:

[0162] (6) Solution C and solution D were added dropwise to mixture E at a rate of 20 mL / min in parallel, and stirring was continued for 30 min after the addition was completed.

[0163] (7) Place the flask in step (6) in a water bath, evaporate the ammonia in the solution at 50°C until the pH value of the solution is 5, filter to obtain a filter cake, and wash the filter cake with deionized water until the pH value of the washing solution is 7.

[0164] (9) The solid F was placed in a tubular furnace and calcined at 400 °C for 8 h in an air atmosphere to obtain a solid catalyst precursor.

[0165] (10) The solid catalyst precursor calcined in step (9) is carbonized in a mixed gas of ammonia, methanol and hydrogen in a volume ratio of 1:4:15. The carbonization conditions are: temperature 320° C., pressure 1.7 MPa, mixed gas space velocity 6000 mL / (g·h), and constant temperature for 18 hours to obtain the desired catalyst.

[0166] Other conditions are the same as in Example 1.

[0167] Embodiment 13

[0168] The preparation steps of FeCo catalyst for Fischer-Tropsch synthesis are as follows:

[0169] (6) Solution C and solution D were added dropwise to mixture E at a rate of 15 mL / min in parallel, and stirring was continued for 30 min after the addition was completed.

[0170] (7) Place the flask in step (6) in a water bath, evaporate the ammonia in the solution at 80°C until the pH value of the solution is 6.5, filter to obtain a filter cake, and wash the filter cake with deionized water until the pH value of the washing solution is 7.

[0171] (9) The solid F was placed in a tubular furnace and calcined at 600 °C for 4 h in an air atmosphere to obtain a solid catalyst precursor.

[0172] (10) The solid catalyst precursor calcined in step (9) is carbonized in a mixed gas of ammonia, methanol and hydrogen in a volume ratio of 3:1:15. The carbonization conditions are: temperature 250°C, pressure 1.5 MPa, mixed gas space velocity 4000 mL / (g·h), and constant temperature for 12 hours to obtain the desired catalyst.

[0173] Other conditions are the same as in Example 1.

[0174] Embodiment 14

[0175] The preparation steps of FeCo catalyst for Fischer-Tropsch synthesis are as follows:

[0176] (9) The solid F was placed in a tubular furnace and calcined at 500 °C for 6 h in an air atmosphere to obtain a solid catalyst precursor.

[0177] (10) The solid catalyst precursor calcined in step (9) is carbonized in a mixed gas of ammonia, methanol and hydrogen in a volume ratio of 2:2:15. The carbonization conditions are: temperature 350°C, pressure 3 MPa, mixed gas space velocity 8000 mL / (g·h), and constant temperature for 48 hours to obtain the desired catalyst.

[0178] Other conditions are the same as in Example 1.

[0179] Embodiment 15

[0180] The preparation steps of FeCo catalyst for Fischer-Tropsch synthesis are as follows:

[0181] (1) Weigh 86.8 g of cerium nitrate hexahydrate, 94.5 g of calcium nitrate tetrahydrate, and 750.3 g of aluminum nitrate nonahydrate and dissolve them in 3 L of deionized water. Stir until all the solids are dissolved. This is referred to as solution A.

[0182] (3) Weigh 80.8 g of ferric nitrate nonahydrate and dissolve it in 500 mL of deionized water. Stir until all the solid is dissolved. This is referred to as solution C.

[0183] (4) 560 mL of 25 wt% ammonia water was measured, 5.9 g of sodium carbonate was added to the ammonia water, and 11.9 g of cobalt carbonate was added to the solution, and stirred until all the solids were dissolved. This was recorded as solution D.

[0184] Other conditions are the same as in Example 1.

[0185] Example 16

[0186] The preparation steps of FeCo catalyst for Fischer-Tropsch synthesis are as follows:

[0187] (2) Prepare a 0.2 mol / L sodium carbonate solution, referred to as solution B.

[0188] (5) Add 3 L of solution B to a 10 L flask, and add solution A dropwise at a rate of 10 mL / min until the solution pH is 6. Continue to add solution B dropwise at a rate of 70 mL / min until the solution pH is 11, continue stirring for 2 h, and filter to obtain a filter cake.

[0189] (6) Solution C and solution D were added dropwise to mixture E at a rate of 25 mL / min in parallel, and stirring was continued for 30 min after the addition was completed.

[0190] (7) Place the flask in step (6) in a water bath, evaporate the ammonia in the solution at 40°C until the pH value of the solution is 7, filter to obtain a filter cake, and wash the filter cake with deionized water until the pH value of the washing solution is 7.

[0191] (8) The washed filter cake was placed in a forced air drying oven at 90°C for 13 h, and then placed in a vacuum drying oven at 40°C for 10 h. The dried solid was ground and sieved to make the solid particles ≤200 mesh, to obtain solid F.

[0192] (9) The solid F was placed in a tubular furnace and calcined at 300 °C for 2 h in an air atmosphere to obtain a solid catalyst precursor.

[0193] (10) The solid catalyst precursor calcined in step (9) is carbonized in a mixed gas of ammonia, methanol and hydrogen in a volume ratio of 1:1:20. The carbonization conditions are: temperature 200° C., pressure 1.3 MPa, mixed gas space velocity 3000 mL / (g-cat.·h), and constant temperature for 50 h to obtain the desired catalyst.

[0194] Other conditions are the same as in Example 1.

[0195] Comparative Example 1

[0196] The purpose is to illustrate the effect of the addition of the first auxiliary agent on the catalytic activity together with Example 1.

[0197] The preparation steps of FeCo catalyst for Fischer-Tropsch synthesis are as follows:

[0198] (1) Weigh 7.7 g of magnesium nitrate hexahydrate and 750.3 g of aluminum nitrate nonahydrate and dissolve them in 3 L of deionized water. Stir until all the solids are dissolved. This is referred to as solution A.

[0199] (2) Prepare a 1.3 mol / L sodium carbonate solution, referred to as solution B.

[0200] (3) Weigh 323.2 g of ferric nitrate nonahydrate and dissolve it in 675 mL of deionized water. Stir until all the solids are dissolved. This is referred to as solution C.

[0201] (4) 1350 mL of 25 wt% ammonia water was measured, 14.3 g of sodium carbonate was added to the ammonia water, and 47.6 g of cobalt carbonate was added to the solution, and stirred until all the solids were dissolved. This was recorded as solution D.

[0202] (5) Add 3 L of solution B to a 10 L beaker, add solution A dropwise at a rate of 30 mL / min until the solution pH = 4.5, continue to add solution B dropwise at a rate of 50 mL / min until the solution pH = 9, continue stirring for 2 h, filter to obtain a filter cake, wash the filter cake with deionized water 9 times, put the washed filter cake into a 10 L beaker, add 6 L of deionized water, and stir to evenly disperse the solids. This is recorded as mixture E.

[0203] (6) Solution C and solution D were added dropwise to mixture E at a rate of 10 mL / min in parallel, and stirring was continued for 30 min after the addition was completed.

[0204] (7) Place the beaker in a water bath and evaporate the ammonia in the solution at 80°C until the pH value of the solution is 6, filter to obtain a filter cake, and wash the filter cake with deionized water until the pH value of the washing solution is 7.

[0205] (8) The washed filter cake was placed in a forced air drying oven at 120°C for 12 hours, and then placed in a vacuum drying oven at 60°C for 12 hours. The dried solid was ground and sieved to make the solid particles ≤ 200 mesh, to obtain solid F.

[0206] (9) The solid F was placed in a tubular furnace and calcined at 500°C for 5 h in an air atmosphere to obtain a solid G.

[0207] (10) Solid D was carbonized in a mixture of ammonia, methanol, and hydrogen in a volume ratio of 5:20:75. The carbonization conditions were: temperature 280 °C, pressure 2.6 MPa, mixed gas space velocity 6000 mL / (g-cat.·h), and constant temperature for 36 h to obtain the desired catalyst.

[0208] Comparative Example 2

[0209] The purpose is to compare with Example 1 to illustrate the effect of the addition of the second auxiliary agent on the catalytic activity.

[0210] The other conditions were the same as those in Comparative Example 1, except that 7.7 g of magnesium nitrate hexahydrate in step (1) was replaced with 2.4 g of copper nitrate trihydrate to obtain a catalyst.

[0211] Comparative Example 3

[0212] The purpose is to compare with Example 1 to illustrate the effect of the addition of the second active metal on the catalytic activity.

[0213] The preparation steps of FeCo catalyst for Fischer-Tropsch synthesis are as follows:

[0214] (1) Weigh 2.4 g of copper nitrate trihydrate, 7.7 g of magnesium nitrate hexahydrate, and 750.3 g of aluminum nitrate nonahydrate and dissolve them in 3 L of deionized water. Stir until all the solids are dissolved. This is referred to as solution A.

[0215] (2) Prepare a 1.3 mol / L sodium carbonate solution, referred to as solution B.

[0216] (3) Weigh 323.2 g of ferric nitrate nonahydrate and dissolve it in 675 mL of deionized water. Stir until all the solid is dissolved. This is referred to as solution C.

[0217] (4) Add 3 L of solution B to a 10 L beaker, add solution A dropwise at a rate of 30 mL / min until the solution pH = 4.5, continue to add solution B dropwise at a rate of 50 mL / min until the solution pH = 9, continue stirring for 2 h, filter to obtain a filter cake, wash the filter cake with deionized water 9 times, put the washed filter cake into a 10 L beaker, add 6 L of deionized water, and stir to evenly disperse the solids. This is recorded as mixture D.

[0218] (5) Solution C was added dropwise to mixture D at a rate of 10 mL / min. After the addition was complete, stirring was continued for 30 min.

[0219] (6) Place the beaker in a water bath and evaporate the ammonia in the solution at 80°C until the pH value of the solution is 6, filter to obtain a filter cake, and wash the filter cake with deionized water until the pH value of the washing solution is 7.

[0220] (7) The washed filter cake was placed in a forced air drying oven at 120°C for 12 hours, and then placed in a vacuum drying oven at 60°C for 12 hours. The dried solid was ground and sieved to make the solid particles ≤ 200 mesh, to obtain solid E.

[0221] (8) The solid E was placed in a tubular furnace and calcined at 500°C for 5 h in an air atmosphere to obtain a solid F.

[0222] (9) Solid F was carbonized in a mixed gas of ammonia, methanol, and hydrogen in a volume ratio of 5:20:75. The carbonization conditions were: temperature 280°C, pressure 2.6 MPa, mixed gas space velocity 6000 mL / (g-cat.·h), and constant temperature for 36 h to obtain the desired catalyst.

[0223] Comparative Example 4

[0224] The purpose is to compare with Example 1 to illustrate the effect of the back-drip step of solution B on the catalytic activity.

[0225] The other conditions were the same as those in Example 1, except that step (5) was changed as follows: 3 L of solution B was added to a 10 L beaker, solution A was added dropwise at a rate of 30 mL / min until the pH of the solution reached 4.5, stirring was continued for 2 h, and a filter cake was obtained by suction filtration. The filter cake was washed 9 times with deionized water to obtain a catalyst.

[0226] Comparative Example 5

[0227] The purpose is to compare with Example 1 to illustrate the effect of the ammonia evaporation step on the catalytic activity.

[0228] The preparation steps of FeCo catalyst for Fischer-Tropsch synthesis are as follows:

[0229] (1) Weigh 2.4 g of copper nitrate trihydrate, 7.7 g of magnesium nitrate hexahydrate, and 750.3 g of aluminum nitrate nonahydrate and dissolve them in 3 L of deionized water. Stir until all the solids are dissolved. This is referred to as solution A.

[0230] (2) Prepare a 1.3 mol / L sodium carbonate solution, referred to as solution B.

[0231] (3) Weigh 323.2 g of ferric nitrate nonahydrate and dissolve it in 675 mL of deionized water. Stir until all the solid is dissolved. This is referred to as solution C.

[0232] (4) 1350 mL of 25 wt% ammonia water was measured, 14.3 g of sodium carbonate was added to the ammonia water, and 47.6 g of cobalt carbonate was added to the solution, and stirred until all the solids were dissolved. This was recorded as solution D.

[0233] (5) Add 3 L of solution B to a 10 L beaker, add solution A dropwise at a rate of 30 mL / min until the solution pH = 4.5, continue to add solution B dropwise at a rate of 50 mL / min until the solution pH = 9, continue stirring for 2 h, filter to obtain a filter cake, wash the filter cake with deionized water 9 times, put the washed filter cake into a 10 L beaker, add 6 L of deionized water, and stir to evenly disperse the solids. This is recorded as mixture E.

[0234] (6) Solution C and solution D were added dropwise to mixture E at a rate of 10 mL / min in parallel. After the addition was completed, stirring was continued for 30 min. The mixture was filtered and washed to obtain a filter cake.

[0235] (7) The washed filter cake was placed in a forced air drying oven at 120°C for 12 hours, and then placed in a vacuum drying oven at 60°C for 12 hours. The dried solid was ground and sieved to make the solid particles ≤ 200 mesh, to obtain solid F.

[0236] (8) The solid F was placed in a tubular furnace and calcined at 500°C for 5 h in an air atmosphere to obtain a solid G.

[0237] (9) Solid D was carbonized in a mixed gas of ammonia, methanol, and hydrogen in a volume ratio of 5:20:75. The carbonization conditions were: temperature 280°C, pressure 2.6 MPa, mixed gas space velocity 6000 mL / (g-cat.·h), and constant temperature for 36 h to obtain the desired catalyst.

[0238] Comparative Example 6

[0239] The monolithic iron-cobalt bimetallic Fischer-Tropsch synthesis catalyst was prepared by the method of Example 1 of comparative document CN105921167.

[0240] The evaluation process and conditions of the catalyst are:

[0241] (1) 10 g of the catalysts prepared in Examples 1 to 16 and Comparative Examples 1 to 6 were placed in a 1 L stirred tank, 750 mL of liquid paraffin was added to the stirred tank, and synthesis gas was introduced to perform Fischer-Tropsch synthesis. The process conditions of the Fischer-Tropsch synthesis reaction were as follows.

[0242] The Fischer-Tropsch synthesis conditions are as follows: the stirred tank is heated to 250°C, synthesis gas H2 / CO (v / v) = 2 is introduced, the space velocity is set to 15000 mL / (g-cat.·h), the synthesis gas is continuously introduced and stabilized for a period of time until the content of each gas phase component in the exhaust gas detection result does not change with time, and then the reaction timing is started.

[0243] The reaction performances of the catalysts prepared in Examples 1 to 16 and Comparative Examples 1 to 6 are shown in Table 1.

[0244] Table 1

[0245]

[0246]

[0247] It can be seen from Table 1 that the FeCo catalyst provided by the present invention (Example 4, Comparative Example 3) has higher CO conversion rate, lower CO2, lower CH4 selectivity, and higher C 5+The selectivity shows that it has high catalytic activity; the catalyst has no obvious deactivation during use, which shows that the catalyst has high catalytic stability.

[0248] By comparing the reaction results of Example 4, Comparative Example 1 and Comparative Example 2, it can be seen that the addition of dual additives can significantly improve the activity and stability of the catalyst, and the catalyst prepared by adding additives Cu and Mg at the same time (Example 4) has the highest reaction activity and stability.

[0249] The catalyst prepared by combining the precipitation method with the ammonia evaporation method (Example 4, Comparative Example 4, Comparative Example 5) has the highest reaction activity and stability. The catalyst prepared by this method has a stable structure, Fe and Co are evenly dispersed, and can effectively prevent the active center elements from agglomerating and sintering.

[0250] From the above description, it can be seen that the above embodiments of the present invention achieve the following technical effects:

[0251] (1) The catalyst prepared by the present invention has two active centers, Fe and Co. Compared with a single active center, the catalyst has a higher reaction activity. The catalyst prepared under the optimal conditions is used to carry out Fischer-Tropsch synthesis experiments, and the CO conversion rate reaches more than 75.69%, and the C 5+ The selectivity was close to 80.95%.

[0252] (2) The catalyst prepared under the optimal conditions did not show any obvious deactivation after long-term use in a stirred tank. The addition of dual additives improved the stability of the catalyst and it has excellent application value.

[0253] (3) The catalyst is prepared by a precipitation-evaporation ammonia addition method, which is simple, low-cost, easy to control the preparation conditions, and easy to realize industrial production.

[0254] (4) The dual active centers are loaded on the carrier in a competitive manner, which effectively reduces the possibility of metal agglomeration in the active centers and improves the activity and stability of the catalyst. The catalyst has high reaction activity and catalytic stability under a wide range of reaction conditions.

[0255] In general, the FeCo catalyst prepared by the preparation method of the present invention has the advantages of high thermal stability, high mechanical strength, high catalytic activity, high selectivity for hydrocarbon products, uniform distribution of active metals, etc., and has good industrial application prospects.

[0256] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a FeCo catalyst, characterized in that: The preparation method comprises: The first auxiliary agent, the second auxiliary agent and the aluminum salt are mixed to perform a coprecipitation reaction to obtain a carrier precursor; Adding the Fe-containing salt solution and the Co-containing ammonia complex solution dropwise to the support precursor for the first time in parallel and stirring for the first time to obtain a mixture; The mixture is subjected to ammonia evaporation, drying and calcination to obtain a FeCo catalyst precursor; The FeCo catalyst is obtained by performing a reduction carbonization reaction on the FeCo catalyst precursor using a mixed gas containing ammonia, methanol and hydrogen.

2. The preparation method according to claim 1, characterized in that: The preparation method of the carrier precursor comprises the following steps: Mixing the first auxiliary agent, the second auxiliary agent, the aluminum salt and deionized water to obtain a solution A; The solution A is added dropwise to the sodium carbonate solution for a second time and stirred for a second time to obtain a suspension B, and the addition is stopped when the pH of the suspension B is 3.5 to 5; Adding the sodium carbonate solution dropwise to the suspension B for the third time and stirring for the third time to obtain a suspension C, and stopping the dropping when the pH of the suspension C is 8.5-10; The suspension C is stirred, filtered and washed for the fourth time to obtain a filter cake; Adding the deionized water into the filter cake to evenly disperse the filter cake to obtain the carrier precursor; Preferably, the concentration of sodium carbonate is 0.5 to 3 mol / L; More preferably, the concentration of sodium carbonate is 1 to 2 mol / L; Preferably, the second dripping speed is 20-40 mL / min; More preferably, the second dripping speed is 25-35 mL / min; Preferably, the third dripping speed is 30-60 mL / min; Preferably, the second stirring speed is 150-400 r / min; Preferably, the speed of the third stirring is 150-400 r / min.

3. The preparation method according to claim 1, characterized in that: The method for preparing the solution of the Co-containing ammonia complex comprises: mixing a Co-containing salt solution and ammonium carbonate-ammonia water to obtain the solution of the Co-containing ammonia complex; Preferably, the Co-containing salt solution is selected from any one of the following: cobalt carbonate, cobalt sulfate or basic cobalt carbonate; Preferably, the molar ratio of Co ions in the Co-containing salt solution to the ammonia water in the ammonium carbonate-ammonia water is: (0.5~1):30。 4. The preparation method according to claim 1, characterized in that: The Fe-containing salt solution is selected from any one of the following: ferric nitrate, ferric sulfate, ferric chloride or ferric acetate; Preferably, the aluminum salt is selected from any one of the following: aluminum nitrate nonahydrate, aluminum sulfate 18hydrate or anhydrous aluminum chloride; Preferably, the molar ratio of iron ions in the Fe-containing salt solution, the Co ammonia complex in the Co ammonia complex solution, and aluminum ions in the aluminum salt is (0.25-0.75):(0.1-0.5):1; More preferably, the molar ratio of the iron ions in the Fe-containing salt solution, the Co ammonia complex in the Co ammonia complex solution, and the aluminum ions in the aluminum salt is (0.4-0.6):(0.15-0.3):1; Preferably, the first dropping speed is 5 to 20 mL / min.

5. The preparation method according to claim 1, characterized in that: The drying includes air drying and vacuum drying; Preferably, the blast drying temperature is 100-140°C and the time is 8-12h; More preferably, the air drying temperature is 110-120°C and the time is 10-12h; Preferably, the vacuum drying temperature is 50-80°C and the time is 12-24h; More preferably, the vacuum drying is carried out at a temperature of 60 to 70° C. and for a time of 15 to 20 hours.

6. The preparation method according to claim 1, characterized in that: The calcination temperature is 400-650° C. and the calcination time is 4-8 hours.

7. The preparation method according to claim 1, characterized in that: The temperature of the ammonia evaporation is 50-80°C; Preferably, the ammonia evaporation is stopped when the pH value of the mixture is 5-6.

5.

8. The preparation method according to claim 1, characterized in that: The first auxiliary agent is selected from any one of the following: a metal salt of Cu, Zn, Ti, Mo, Ce or Mn; Preferably, the second auxiliary agent is selected from any one of the following: magnesium nitrate, barium nitrate, calcium nitrate or strontium nitrate; Preferably, the molar ratio of the metal ions in the first auxiliary agent, the metal ions in the second auxiliary agent and the aluminum ions in the aluminum salt is (0.005-0.05):(0.01-0.1):1; More preferably, the molar ratio of the metal ions in the first auxiliary agent, the metal ions in the second auxiliary agent and the aluminum ions in the aluminum salt is (0.02-0.03):(0.05-0.08):

1.

9. The preparation method according to claim 1, characterized in that: The volume ratio of the ammonia, the methanol and the hydrogen is (1-3):(1-4):15; Preferably, the reaction conditions of the reduction carbonization are: mixed gas space velocity of 4000-8000 mL / (g-cat.·h), temperature of 250-350° C., pressure of 1.5-3 MPa, and time of 12-48 h.

10. Use of the FeCo catalyst prepared by the preparation method according to any one of claims 1 to 9 in Fischer-Tropsch synthesis.

Citation Information

Patent Citations

  • Novel Fischer Tropsch synthesis method

    CN102441386A

  • A Fischer-Tropsch iron-based catalyst with high wear resistance and high reactivity and its preparation method.

    CN105478128B